Phenotypes including immunocompetence in scavenging local chicken ecotypes in Tanzania - Msoffe, P.L.M.; Minga, U.M.; Olsen, J.E.; Yongolo, M.G.S.; Juul-Madsen, H.R.; Gwakisa, P.S.; Mtambo, M.M.A. (Springer, 2001)
A study was conducted to determine the variations in physical characters and immunocompetence among scavenging local chicken ecotypes in Tanzania. Eighty-four adult scavenging local chickens from four eco-climatic regions of Tanzania were studied. Measurements of adult body weight, body length, shank length and egg weight and observations of plumage colour and pattern, earlobe colour, skin colour and the shape of the comb were conducted. The antibody response to sheep red blood cells, serum haemolytic complement and the cutaneous response to phytohaemagglutinin-P were assessed. Five ecotypes were identified nd named Mbeya, Morogoro-medium, Ching'wekwe, Kuchi and Singamagazi. Singamagazi and Kuchi were significantly heavier, with longer shanks and heavier eggs than the other ecotypes. The average adult body weight for males ranged from 1621 g (Mbeya) to 2915 g (Singamagazi). Average female weights ranged from 1108 g (Morogoro-medium) to 2020 g (Singamagazi). Mean egg weights ranged from 37.65 g (Ching'wekwe) to 45.61 (Singamagazi). The Kuchi had mostly rose and walnut combs, while the other ecotypes were mostly single combed. In each ecotype there were chickens with a high or low antibody response to red blood cells, but there was a significant difference between the ecotypes.